2000
DOI: 10.1007/s002130000409
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the nicotinic antagonist mecamylamine on inspection time

Abstract: The slowing of inspection time following mecamylamine is consistent with the role of nAchRs in speed of information processing, and add to the evidence that IT may in part index nAchR system integrity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
33
2

Year Published

2001
2001
2009
2009

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 17 publications
6
33
2
Order By: Relevance
“…After donepezil ingestion visual IT improved at 90 min post-drug, before peak-plasma concentration, supporting earlier findings with donepezil at this very period after drug ingestion (Hutchison et al, 2001), and with nicotinic agonists (Stough et al, 1995;Thompson et al, 2000), as well as partial improvement with donepezil following nicotinic receptor antagonism (Thompson et al, 2000). These positive changes in IT following donepezil may reflect enhanced selective visual attention at encoding that has been related to increases in acetylcholine (Hasselmo and Stern, 2006;Furey et al, 2000aFurey et al, ,b, 2008a, or more specifically increases in bottom-up attentional processing (see Furey et al, 2008b).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…After donepezil ingestion visual IT improved at 90 min post-drug, before peak-plasma concentration, supporting earlier findings with donepezil at this very period after drug ingestion (Hutchison et al, 2001), and with nicotinic agonists (Stough et al, 1995;Thompson et al, 2000), as well as partial improvement with donepezil following nicotinic receptor antagonism (Thompson et al, 2000). These positive changes in IT following donepezil may reflect enhanced selective visual attention at encoding that has been related to increases in acetylcholine (Hasselmo and Stern, 2006;Furey et al, 2000aFurey et al, ,b, 2008a, or more specifically increases in bottom-up attentional processing (see Furey et al, 2008b).…”
Section: Discussionsupporting
confidence: 85%
“…In the present study, an acute oral dose of 5 mg of donepezil improved performance in various cognitive domains (visual IT, episodic memory for verbal prose, memory for objects, for location of objects in space and binding of object identities to spatial positions, and recall of digits in backwards order), extending previous data on the acute nootropic potential of this drug in young, healthy volunteers (Thompson et al, 2000;Hutchison et al, 2001). As none of the measures used here involved limited time to respond, the non-specific decrease in reaction times that can occur for many acetylcholine agonists (e.g., Meinke et al, 2006) cannot account for the nootropic effects of donepezil in the present study.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In order to examine if medication has an effect on IT in depression, medicated and unmedicated subjects were grouped separately in the present study. As our previous research has indicated that anticholinergic drugs can impair IT (Thompson et al 2000 ;Waterham et al 2002), we compared patients receiving antidepressants with anticholinergic effects to those receiving antidepressants with minimal anticholinergic actions. Depressive symptoms and history have also been reported by some studies to be related to cognitive impairment in some studies (Austin et al 1992) but not others (Purcell et al 1997 ;Schatzberg et al 2000), thus the relationship between level of depression, depressive history and IT were examined.…”
Section: Introductionmentioning
confidence: 99%